IMPLEMENTACIÓN CONTABLE EN EL “SUPERMERCADO LISSETH” DE LA CIUDAD DE CARIAMANGA, PERÍODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2020 - Jiménez Flores, María Cristina (2021)
The thesis work entitled: ACCOUNTING IMPLEMENTATION IN THE “LISSETH SUPERMARKET” OF THE CITY OF CARIAMANGA, PERIOD FROM SEPTEMBER 01 TO DECEMBER 31, 2020 was developed taking into account the need of the microenterprise to collect, organize and record all the information of their economic movements in an efficient way, thus allowing to obtain real information on the economic - financial situation. Through the accounting process to the supermarket, each of the proposed objectives was met, for the first objective, the design of a plan and manual of accounts was proposed according to the economic activities of the microenterprise, which facilitates the identification of each economic movement and the accounting accounts to be used in the development of the practical work; In the same way, the initial inventory was structured. For this, it was necessary to organize and classify all the goods, securities, obligations and other economic and financial information that the microenterprise has For the third and fourth objectives, auxiliary record formats were designed for sales, for acquisitions made by the microenterprise, for accounts receivable for outstanding customer balances, Kardex cards to establish the actual stock of merchandise and roles. payment and provisions to establish salary values; and finally for the fifth objective, the accounting process was developed from the source documentation, the Initial Inventory, The Initial Situation Statement, the recording of economic operations in the journal, the account balances in the general ledger, the sums totals in the trial balance, the respective adjustments in the worksheet and obtaining the Statement of Economic Situation, the Statement of Financial Situation and the Cash Flow Statement